HOW THE IMPLEMENTATION OF LENDING FIDUCIARY GUARANTEE? - Hartanto Hartanto; Fatmasari Wulandari; Ratih Mega Puspasari (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2019)
Lending by banks basically have an assurance bank of capability and debtors to repay their debts, and must be conducted on the basis of the principle of sound lending and the precautionary principle so that the credit does not harm the interests of the bank, customers debtor and the public depositors. It must be implemented, given the bank's loans to risk that is not returned in accordance with the agreement. One of the factors that would cause the value of bad loans is not comparable to a loan guarantee. In the banking world generally embraced the concept of an assessment of the highest collateral 80% of the value of the collateral, and the loan amount can be given is 80% of the value of the collateral.Keywords: Fiduciary; Credit; Implementation.